2019
DOI: 10.3390/ma12172707
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilica Extracted from Hexafluorosilicic Acid of Waste Fertilizer as Reinforcement Material for Natural Rubber: Preparation and Mechanical Characteristics

Abstract: Nanosilica particles are extracted from waste water containing a hexafluorosilicic acid discharged from Vietnamese fertilizer plants as an effective way not only to reduce waste water pollution but also to enhance the value of their waste water. Amorphous nanosilica particles are produced with diameters ranging from 40 to 60 nm and then adopted as a reinforcing additive for natural rubber (NR) composites. Morphological, mechanical, rheological, and thermal behaviors of the nanosilica-added NR composites are ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…FSA spillage in a water body affects the local ecosystem reducing the pH level and increasing the fluorine concentration. Due to its limited market (i.e., FSA is typically used in some niche applications, such as either water fluorination or the production of AlF 3 ) and the increasing legislation to regulate its disposal, both industrial and academic research are focusing their attention on the possible reuse of FSA, in particular, the synthesis of various Si-based materials [ 156 , 157 , 158 ].…”
Section: Silica From Industrial Production Waste or End-of-life Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…FSA spillage in a water body affects the local ecosystem reducing the pH level and increasing the fluorine concentration. Due to its limited market (i.e., FSA is typically used in some niche applications, such as either water fluorination or the production of AlF 3 ) and the increasing legislation to regulate its disposal, both industrial and academic research are focusing their attention on the possible reuse of FSA, in particular, the synthesis of various Si-based materials [ 156 , 157 , 158 ].…”
Section: Silica From Industrial Production Waste or End-of-life Productsmentioning
confidence: 99%
“…The obtained solid was purified by washing it with water and then, finally, spray-dried. Nguyen et al [ 157 ] reported a process based on the reaction between FSA and a 20 wt.% ammonia solution at RT for 12 h under mechanical stirring to obtain a slurry with suspended SiO 2 . The SiO 2 formation mechanism reported by Vacca et al [ 64 ] consisted of a typical acid–base reaction where the intermediate ammonium hexafluoro silicate (NH 4 ) 2 SiF 6 almost immediately reacted, precipitating as SiO 2 , leaving in the aqueous phase ammonium fluoride (NH 4 F) as a secondary product.…”
Section: Silica From Industrial Production Waste or End-of-life Productsmentioning
confidence: 99%
“…19) with an annual growth of 5.6%. 20 Chemical and biogenic synthesis are the most common techniques for the synthesis of silica nanoparticles. The chemical route has some undesirable characteristics: it produces some toxic compounds, is expensive, has high-energy consumptions, while the biogenic processes are cheaper, energy-saving, and eco-friendly for commercial-scale syntheses.…”
Section: Silica-based Nanomaterials and Its Applicationsmentioning
confidence: 99%
“…Nguyen and coworkers reported a method of recovering amorphous silica nanoparticles (40-60 nm) from hexafluorosilicic acid waste (Vietnamese fertilizer industry) through a precipitation process [17]. These particles were adopted as a reinforcing filler of natural rubber (NR) materials, which were characterized by morphological, mechanical, rheological and thermal measurements.…”
Section: Waste Products For Construction Materialsmentioning
confidence: 99%
“…For that purpose, six papers were related to the preparation of innovative composite materials. Specifically, five papers reported the reuse of end-of-life tire rubber, porous glass, expanded polystyrene, slags, fly ashes and sheep's wool fibers for the preparation of cement conglomerates [12][13][14][15][16], while the last one reported the reuse of amorphous silica nanoparticles for the preparation of composites with natural rubber [17]. Moreover, five papers were related to the treatment of wastes for environmental applications.…”
Section: Introductionmentioning
confidence: 99%